PENGARUH FAKTOR INTERNAL DAN EKSTERNAL INDIVIDU TERHADAP MINAT INVESTASI REKSADANA PADA MAHASISWA FEB UNIVERSITAS DIPONEGORO - Pretty Dayana Mashita Toris; Fuad Fuad (Diponegoro Journal of Accounting, 2025)
This study examines the influence of internal factors (Financial Literacy and Investment Motivation) and external factors (Capital Market Socialization and Investment Return) on Mutual Fund Investment Interest among students at Diponegoro University, as well as identifying the most dominant factor among them. It is hypothesized that both internal and external factors positively influence Mutual Fund Investment.The study involved a sample of 150 Diponegoro University students collected through a questionnaire during a specific research period. The sample was selected using purposive sampling, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software.The analysis results show that Financial Literacy, Investment Motivation, and Capital Market Socialization have a positive and significant influence on Mutual Fund Investment Interest. Meanwhile, Investment Return does not have a significant effect. Among the significant variables, Investment Motivation is the most dominant factor, followed by Financial Literacy and Capital Market Socialization. These findings indicate that students' personal motivation and financial understanding, supported by capital market education, are the primary drivers shaping their interest in mutual fund investment.